Discharge against medical advice in the neonatal unit of Rivers State University Teaching Hospital, Nigeria: a two-year prospective study - West, Boma Awoala; Briggs, Datonye Christopher (International Journal of Contemporary Pediatrics, 2023)
Background: Discharge against medical advice (DAMA) is a silent contributor to neonatal morbidity and mortality in Nigeria. Parents’ autonomous decision to discontinue medical care of their babies admitted remains an ethical contention that is frustrating for pediatricians and portends poor neonatal outcomes. DAMA remains a challenge arising from an interplay of parental and hospital-related factors. Hence, epidemiologic data are needed, where none previously exists. Aim of the study was to determine the prevalence, neonate and family sociodemographic characteristics, morbidity pattern and reasons for DAMA among neonates admitted to the Rivers State University Teaching Hospital. Methods: A prospective observational study was conducted among neonates admitted from April 2021 to March 2023. Results: Of 1830 neonatal admissions, 87 were discharged against medical advice giving a DAMA prevalence of 4.8%, of which 48 (55.8%) were females. Most, 66 (75.9%) were born at term, 51 (58.6%) had normal birth weight, 38 (43.7%) admitted at <2 hours of life and (41.4%) were above 2nd birth order. Forty-seven (54%) of mothers, 41 (47.1%) of fathers had tertiary education and 61 (70.1%) were of low/middle socioeconomic class. Neonatal sepsis (61.2%) and neonatal jaundice (31.8%) were the commonest morbidities. Most, 65 (74.7%) of DAMA cases occurred in the 1st week of life and the father 63 (73.3%) was the main requestor of DAMA. The commonest reason for DAMA was financial constraints 50 (57.5%). Conclusions: The prevalence of DAMA was 4.8%. Neonatal sepsis and neonatal jaundice were the commonest morbidity with financial constraints being the main reason for DAMA. The father was the requestor for DAMA in the majority of the cases.